Studi Literatur: Peran Dosen Kewirausahaan dalam Mendorong Komersialisasi Produk Hasil Penelitian Biologi - sanusi; Armiyani (Universitas Muslim Buton, 2025)
Higher education institutions play a crucial role not only in producing research but also in ensuring that research outcomes can be effectively utilized by society. In the field of biology, innovations such as functional foods, biofertilizers, and natural pharmaceutical raw materials are frequently developed, yet they often remain at the publication or laboratory prototype stage due to insufficient support in non-technical aspects, including business strategy, marketing, and intellectual property rights protection. Entrepreneurial lecturers have a strategic role in overcoming these barriers by helping researchers and students understand market potential, design appropriate business models, and facilitate collaborations with industry or investors. This study employs a literature review method to examine the role of entrepreneurial lecturers in promoting the commercialization of biological research products. The findings indicate that lecturers act as innovation facilitators, curriculum integrators for entrepreneurship, and network enhancers, thereby accelerating the transformation of research into commercial products. Identified challenges include limited business knowledge among researchers, minimal regulatory support for intellectual property rights, and restricted access to funding and industry partners. Recommended strengthening strategies include interdisciplinary collaboration, research-based business management training, and the establishment of innovation centers within universities. With a structured innovation ecosystem, biological research outcomes have greater potential for commercialization, generating economic value and tangible socio-economic impact.